The collected works of Henrik Ibsen, Vol. 02 (of 11) - Ibsen, Henrik; Ibsen, Enrico; Ibsen, Henryk (Project Gutenberg, 2021)
The vikings at Helgeland (translated by William Archer) -- The pretenders (translated by William Archer).